System rezerw na ryzyko kredytowe w instytucjach kredytowych Hiszpanii - Orzeszko, Teresa (Reserves System on Credit Risk in Credit Institutions in Spain, 2006)
Among various factors determining safety and stability of credit institutions a significant role is played by credit risk provisions. In spite of the fact that they constitute a generally known and applied instrument of fighting risk, principles of their functioning have not been harmonized in an international scale, as yet and therefore they differ in particular countries in many ways. Spain is one of the countries where credit risk provisions are specially regulated by bank accounting regulations issued by the central bank, which also thoroughly and regularly controls the correctness of their application by credit institutions, which to a great extent limits their freedom in shaping these provisions' level and structure. Apart from significant formalization, another characteristic feature of credit risk provisions in Spain becomes the fact that they do not constitute a homogenous category, but cover a few kinds of provisions which supplement one another and therefore construct a cohesive system. This system is made up of specific provisions, general provisions, statistical provisions, called jointly insolvency provisions and country-risk provisions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (5); 2006; nr 1120, s. 27-44